Efforts of Dian Abadi Shop In Maintaining Customer Interest: Upaya Toko Dian Abadi Dalam Mempertahankan Minat Pelanggan - Erince Murib; Yahya Antu; Tety Thalib (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This type of research is a descriptive qualitative approach while the purpose of the study is to find out firsthand how the efforts of the eternal dian store in maintaining customer interest by using the focus including price, location and availability of goods. Based on the results of the study concluded that; Efforts made by the eternal dian store in Gorontalo city from the aspect of price are quite good because they are still the same as market prices. However, there are also consumers who are not satisfied with this price at Toko Dian Abadi so that they make customers buy at other stores. The location of Toko Dian Abadi is very good and strategic, but when the construction of the central market area becomes an obstacle for the shop owner. Customer access to the building location of Toko Dian Abadi gorontalo city. The availability of goods at Dian Abadi Store is still not optimal, the items needed by consumers are not all available at Dian Abadi Store so that consumers go to other stores. It is recommended for Dian Abadi Store to be able to maintain equal price competitiveness with building stores in Gorontalo, Pay attention to the location of the store during the construction of the central market, Pay attention to the availability of goods at Dian Abadi Store so that customers do not go to other stores